Low lipids, CLA fortified diets fed to growing-finishing heavy pigs: effects on subcutaneous fat fatty acid composition - Della Casa, Giacinto; Cavallucci, Clarita; Faeti, Valerio; Marino, Antonio; Marchetto, Gianni; Bochicchio, Davide; Comellini, Michele (Progress in Nutrition, 2014)
Growing-finishing heavy pigs were fed diets containing different amounts of ether extract. Control diet (C ) were based on corn (50%), whereas D diet were based on degermed corn and was fortified in the finishing period with conjugated linoleic acid (CLA). Rearing, slaughtering and jointing performances did not show any difference.  Diet D increased the fatty acid saturation of the  thighs covering subcutaneous fat; palmitic and stearic acid percentages increased, oleic and linoleic percentages and Iodine number decreased. Sensory evaluation of ham covering fat diet showed fats firmer and less oily for diet D vs diet C. The onset of “cured fat” smell was delayed in diet D hams.